2017
DOI: 10.1111/cdev.12946
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Stress Attenuate the Relation Among Adverse Life Events, Perceived Distress, and Self‐Control

Abstract: Prior research has shown that adverse events in the lives of adolescents precipitate psychological distress, which in turn impairs self-control. This study (N = 1,343) examined the protective effects of stress mindsets-beliefs about the extent to which stress might be beneficial or strictly detrimental. The results confirmed that increasing the number of adverse life events across the school year predicted rank order increases in perceived distress, which in turn predicted rank order decreases in self-control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 58 publications
10
75
0
2
Order By: Relevance
“…We find that mindsets on stress, failure, and willpower were significantly correlated with each other (rs > 0.20, ps < 0.007; see Table 2). It is notable that participants reported greater stress-is-enhancing mindsets than populations studied in the past (e.g., Crum et al, 2013;Park et al, 2017). This may be due to self-selection into this extremely stressful environment, social desirability effects, or a combination of these factors.…”
Section: Baseline Survey Correlationsmentioning
confidence: 91%
See 1 more Smart Citation
“…We find that mindsets on stress, failure, and willpower were significantly correlated with each other (rs > 0.20, ps < 0.007; see Table 2). It is notable that participants reported greater stress-is-enhancing mindsets than populations studied in the past (e.g., Crum et al, 2013;Park et al, 2017). This may be due to self-selection into this extremely stressful environment, social desirability effects, or a combination of these factors.…”
Section: Baseline Survey Correlationsmentioning
confidence: 91%
“…In environments with prolonged and highintensity demands, are stress mindsets still beneficial? Some research has suggested that these mindsets may be even more impactful during extreme stress (Akinola et al, 2016;Park et al, 2017). Other research has suggested the opposite -that mindsets cannot override physiological limits during extreme challenges (Vohs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work extended the mindset approach to understand health behaviors including exercise intentions (Orvidas et al, 2018), dieting goal persistence (e.g., Burnette, 2010), addiction treatment intentions (Burnette et al, 2019), coping strategies for psychological distress (Park et al, 2017), and smoking cessation (Kauffman et al, 2017). For example, inducing a growth mindset about weight served as a buffer against weightgain following severe dieting setbacks (Burnette and Finkel, 2012) and predicted healthier food choices (Ehrlinger et al, 2017).…”
Section: Mindsetsmentioning
confidence: 99%
“…Generalized stress beliefs have mainly been studied using two psychometrically evaluated self-report questionnaires: The Stress Mindset Measure (SMM) by Crum et al [22] uses a unidimensional, bipolar scale to assess whether individuals generally believe stress to be enhancing or debilitating. Previous research found that positive stress mindsets were associated with reduced distress in response to adverse life events in adolescents throughout one school year [23], with lower perceived stress, favorable well-being and better academic performance in undergraduate university students [24], and with increased vigor and task performance as well as decreased anxiety and depression in employees [22,25]. More recently, the Beliefs About Stress Scale (BASS) [26] was developed to assess stress beliefs using a multidimensional approach, i.e.…”
Section: The Effects Of Stress Beliefs On Daily Affective Stress Respmentioning
confidence: 97%